Amine-Functionalized Covalent Organic Framework for Efficient SO2 Capture with High Reversibility - Lee, Gang-Young; Lee, Joohyeon; Huyen Thanh Vo; Kim, Sangwon; Lee, Hyunjoo; Park, Taiho (NATURE PUBLISHING GROUP, 2017)
Removing sulfur dioxide (SO2) from exhaust flue gases of fossil fuel power plants is an important issue given the toxicity of SO2 and subsequent environmental problems. To address this issue, we successfully developed a new series of imide-linked covalent organic frameworks (COFs) that have high mesoporosity with large surface areas to support gas flowing through channels; furthermore, we incorporated 4-[(dimethylamino)methyl]aniline (DMMA) as the modulator to the imide-linked COF. We observed that the functionalized COFs serving as SO2 adsorbents exhibit outstanding molar SO2 sorption capacity, i.e., PI-COF-m10 record 6.30 mmol SO2 g(-1) (40 wt%). To our knowledge, it is firstly reported COF as SO2 sorbent to date. We also observed that the adsorbed SO2 is completely desorbed in a short time period with remarkable reversibility. These results suggest that channel-wall functional engineering could be a facile and powerful strategy for developing mesoporous COFs for high-performance reproducible gas storage and separation.
Keywords: IONIC LIQUIDS; SULFUR-DIOXIDE; CO2 CAPTURE; SUBSEQUENT UTILIZATION; CARBON-DIOXIDE; CRYSTALLINE; ABSORPTION; ADSORPTION; SOLUBILITY; STORAGE